A preliminary analysis of various testing techniques in Agile development - A systematic literature review - Thangiah, M. (Institute of Electrical and Electronics Engineers Inc., 2016)
There are numerous software development and testing methods, tools and techniques have emerged over the past few decades with the main objective are to enhance the software quality. In Small and Medium size Enterprises (SME's), Agile methods have been gaining acceptance but quality of the product it produced is remains as the major concern because the tesing methods and standards are not improved. In Agile development process, though there are many testing techniques are exists, SME's cannot afford to follow the traditional methods of testing process, because of high cost and it is a time consuming process. In this research paper, only the issues surfaced in Regression Testing and Automated Testing are analysed and proposed that exploratory testing (ET) methods either can be used as an alternative or can be integrate along with the existing testing methods. However, there is not enough research work is conducted on Exploratory testing and emphasized the importance to focus more research work to be carried out in ET. Â© 2016 IEEE.